NKp46+ natural killer cells attenuate metabolism‐induced hepatic fibrosis by regulating macrophage activation in mice. Issue 3 (21st January 2016) - Tosello‐Trampont, Annie‐Carole; Krueger, Peter; Narayanan, Sowmya; Landes, Susan G.; Leitinger, Norbert; Hahn, Young S.
Abstract : Nonalcoholic steatohepatitis (NASH) affects 3%‐5% of the U.S. population, having severe clinical complications to the development of fibrosis and end‐stage liver diseases, such as cirrhosis and hepatocellular carcinoma. A critical cause of NASH is chronic systemic inflammation promoted by innate immune cells, such as liver macrophages (Mϕ) and natural killer (NK) cells. However, little is known about how the crosstalk between Mϕ and NK cells contributes to regulate NASH progression to fibrosis. In this report, we demonstrate that NKp46 + cells play an important role in preventing NASH progression to fibrosis by regulating M1/M2 polarization of liver Mϕ. Using a murine model of NASH, we demonstrate that DX5 + NKp46 + NK cells are increased during disease and play a role in polarizing Mϕ toward M1‐like phenotypes. This NK's immunoregulatory function depends on the production of interferon‐gamma (IFN‐γ), but not by granzyme‐mediated cytolytic activity. Notably, depletion of NKp46 + cells promotes the development of fibrosis with increased expression of profibrogenic genes as well as skewed M2 Mϕ phenotypes in hepatic tissues. Conclusions: NK cell‐derived IFN‐γ may be essential for maintaining a balanced inflammatory environment that promotes tissue integrity and limiting NASH progression to fibrosis. (Hepatology 2016;63:799–812)